2012
DOI: 10.1016/j.tibtech.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Escherichia coli to synthesize free fatty acids

Abstract: Fatty acid metabolism has received significant attention as a route for producing high-energy density, liquid transportation fuels and high-value oleochemicals from renewable feedstocks. If microbes can be engineered to produce these compounds at yields that approach the theoretical limits of 0.3–0.4 g/g glucose, then processes can be developed to replace current petrochemical technologies. Here, we review recent metabolic engineering efforts to maximize production of free fatty acids (FFA) in Escherichia coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
165
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(167 citation statements)
references
References 78 publications
2
165
0
Order By: Relevance
“…The deletion of fadD, encoding an acyl-CoA synthetase, has been utilized in numerous studies to facilitate the accumulation of longer-chain carboxylic acids by preventing the uptake/activation of free fatty acids (14). Under these conditions, the deletion of fadD in JC01(DE3) atoB CT5 fadBA CT5 with pETDuet-fabI resulted in the extracellular production of 19.4 Ϯ 0.1 mg/liter tetradecanoic acid (C 14 ) and a slight increase in dodecanoic acid (C 12 ), with minimal impact on the levels of C 4 to C 10 carboxylic acids produced (Fig.…”
Section: Ct5mentioning
confidence: 99%
See 1 more Smart Citation
“…The deletion of fadD, encoding an acyl-CoA synthetase, has been utilized in numerous studies to facilitate the accumulation of longer-chain carboxylic acids by preventing the uptake/activation of free fatty acids (14). Under these conditions, the deletion of fadD in JC01(DE3) atoB CT5 fadBA CT5 with pETDuet-fabI resulted in the extracellular production of 19.4 Ϯ 0.1 mg/liter tetradecanoic acid (C 14 ) and a slight increase in dodecanoic acid (C 12 ), with minimal impact on the levels of C 4 to C 10 carboxylic acids produced (Fig.…”
Section: Ct5mentioning
confidence: 99%
“…Among the aforementioned pathways, the bacterial type II fatty acid biosynthesis system (FAB II) (13) is probably the most widely engineered and has been harnessed for the synthesis of many products, including fatty acids (14), fatty acid methyl esters (15), fatty acid ethyl esters (11,16), fatty alcohols (11), and alkanes (12). At the core of the FAB II system is an elongation cycle that uses discrete enzymes to catalyze each of its four steps.…”
mentioning
confidence: 99%
“…In E coli, thioesterases cleave acyl-ACPs producing the free fatty acids necessary for regulatory signals, export or degradation (Lennen and Pfleger, 2012). The fatty acid composition of E. coli expressing Camelina acyl-ACP thioesterase genes were analyzed and compared with control cells transformed with the empty pQE-80L vector (Table 3).…”
Section: Fatty Acid Analysis Of E Coli Expressing Camelina Sativa Acmentioning
confidence: 99%
“…These results showed that C. sativa thioesterases alter E. coli fatty acid metabolism, diverting the acyl chains away from the fatty acid and lipid biosynthetic pathways. These free fatty acids would later be secreted or degraded in the β-oxidation pathway (Lennen and Pfleger, 2012). The main change in the E. coli fatty acid composition when CsFatA was expressed was the reduction in unsaturated fatty acids, mainly oleic acid (18:1ω9).…”
Section: Fatty Acid Analysis Of E Coli Expressing Camelina Sativa Acmentioning
confidence: 99%
“…Fatty acids can be reduced to aldehydes and can then be subjected to decarbonylation, sequential reduction, or decarboxylation to produce equivalent alkanes as petroleum distillates ( Fig. 3) (Lennen and Pfleger 2012). Fatty acid biosynthesis is one of the anabolic pathways capable of producing large hydrophobic fatty acid molecules and their derivatives (Fig.…”
Section: Fats Lipids and Estersmentioning
confidence: 99%